Electronic, magnetic, and mechanical properties of co-doped GaSb: A promising diluted magnetic semiconductor - Samant, Ramnath; Saraf, Deepashri; Adhikari, Rajendra P.; Shilkar, Omkar; Raikar, Sakshit; Silveira, Allan; Sawant, Manthan; Sappati, Subrahmanyam; Joshi, Niharika; Desai, Ashish M. (Journal of Magnetism and Magnetic Materials, 2025)
{Understanding the interplay between magnetism and the electronic structure is crucial for the development of novel spintronic materials. This study employs density functional theory (DFT) calculations to investigate these properties in cubic Gallium Antimonide (GaSb) doped with Cobalt (Co) (Ga1-xCoxSb
Keywords: Density functional theory; Dilute magnetic semiconductors; Electronic properties; GaSb; mechanical properties; Spintronic materials